High-resolution grain size analysis of sediment core IZN_19-21 from Lake Iznik (NW Turkey) - Renaldo Gastineau; Julia De Sigoyer; Pierre Sabatier; Stefano C Fabbri; Flavio S Anselmetti; Anne-Lise Develle; Mustafa Şahin; Serkan Gündüz; Frank Niessen; Andrea Catalina Gebhardt (PANGAEA, 2020)
The grain-size distribution of the sediment was determined in 2019, following a mean of 5 cm sampling step all along the longest sequence (IZN_19_21). As the sequence contains sporadic mm-thick sandy deposits, the resolution in these parts was increased to 0.5 cm. A Beckman Coulter Life Science 13 230 XR laser particle-size analyzer was used (EDYTEM Laboratory, University Savoie Mont Blanc) with sonication to avoid particle flocculation. Two runs with a 30s-long measurement were applied for each fresh sample.